Effect of L-carnitine on sperm parameters in patients with Thalassemia major: A pilot study - Kiumarsi, Azadeh; Hesabi, Amir; Tavanayan, Masoumeh; Amirkashani, Davoud; Azarkeivan, Azita; Molavi, Mohammad Ali (Asian Journal of Pharmaceutical Research and Development, 2020)
Background: More than one-half of men with transfusion dependent thalassemia major (TDTM) are dealing with decreased fertility potentials. As antioxidants such as L-carnitine were reported to improve fertility in healthy males, we aimed to assay the effect of L-carnitine on sperm parameters in adult males with TDTM. Materials and Methods: Twenty six male TDTM patients older than 18 years were included in a pilot study, all had semen analysis; 3 were found to be azoospermic and were excluded. So further analysis for sperms and DNA defects was conducted on the remaining 10 participants. Participants were then given L-carnitine for 3 months. All sperm parameters were reassessed after therapy. Results: In patients with low volume ejaculation, the mean volume of semen increased significantly (p=0.034). In oligospermic patients with a mean sperm concentration of 4.62 million/mL, the mean sperm concentration raised to 22.50 million/mL after therapy (p=0.008). In patients who had lower than normal sperm motility percentage and sperm progressive motility percentage, both variables raised after therapy. Conclusion: Thalassemia major patients showed significant increase in sperm concentration and sperm motility with the use of L-carnitine.